Cycle by cycle NOx model for diesel engine control. (5th January 2017) - Guardiola, C.; Martín, J.; Pla, B.; Bares, P.
Highlights: A method for inferring NOx emissions from in-cylinder pressure signal is presented. Sensor errors (aging or malfunctions) are avoided by relying only on in-cylinder pressure data. The method has one cycle resolution, allowing good transient NOx estimation. The presented method improves precision of current algorithms in 25%. The model can be used for replace or improve Smart NOx sensor information. Abstract: This paper presents a model for on-line NOx estimation. The method uses both, low frequency components and high frequency components of in-cylinder pressure signal: it harnesses in-cylinder pressure resonance to estimate the trapped mass, and based on this measurement, a NOx model is adapted to estimate NOx emissions cycle by cycle. In addition of the in-cylinder pressure signal, the procedure only requires from lambda and air mass flow to estimate NOx, so it can give a direct estimation of NOx or improve transient response and aging of current NOx sensors. The method was validated on a CI engine with high pressure EGR loop under steady and transient conditions showing errors below 10% and cycle by cycle time response.